RESPON PESERTA DIDIK TERHADAP MODEL PEMBELAJARAN BERBASIS OTAK (MPBO) DALAM PEMBELAJARAN MEMBACA PEMAHAMAN - Kohar, Dadun (UNIB Press, 2022)
The purpose of this study was to determine student responses to the Brain-Based Learning Model (MPBO) in learning reading comprehension. This research method is qualitative. Data collection techniques using questionnaires or questionnaires in the form of a Likert scale. The data for each variable is processed by the following steps: grouping the data, tabulating the data, displaying the data in tabular form, calculating scores, displaying the data in the form of pictures, and drawing conclusions for each variable and as a whole. This study concludes that students consider MPBO to be good when used in learning reading comprehension. This can be seen from the perception score given by students, which is 424. If it is presented, the score becomes 84.50%. That is, that the perceptions of students are slightly agree.